Pendidikan Kesehatan Tentang Kesehatan Reproduksi Remaja dan Dampak Seks Bebas pada Remaja di Man 2 Ciamis - Elis Roslianti; Yanti Srinayanti; Neli Sunarni; Ade Raina (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: Adolescent reproductive health is defined as the physical and psychological well-being of a teenager, including freedom from unwanted pregnancy, unsafe abortion, sexually transmitted diseases (STDs) including HIV/AIDS, and all forms of sexual violence and coercion. Objective: This outreach activity was carried out with the aim of increasing the knowledge of Man 2 Ciamis students about how to maintain reproductive health by avoiding casual sex to avoid sexual diseases such as HIV/AIDS. Method: The community service method is carried out by means of counseling and discussions with MAN 2 Ciamis students. Result: It can be concluded that before the health education was implemented, 13 participants (36%) were able to answer questions. And after the presentation was delivered, the participants' knowledge increased to 92% who were able to answer questions. So, this significant participant understanding shows the effectiveness of the material that has been delivered. Conclusion: After carrying out this outreach activity, there was a significant increase in the knowledge of Man 2 Ciamis students regarding the material that had been discussed, namely reproductive health and the impact of casual sex on teenagers. This can be seen from the participants' activeness in participating in health education activities which are useful for preventing and overcoming promiscuity among teenagers which can result in sexually transmitted diseases including HIV/AIDS.